OVERVIEW OF FINANCIAL INCLUSION AS A DETERMINANT OF POVERTY REDUCTION IN MALAYSIA - Solehah Yahaya; Nik Safiah Nik Abdullah; Nadzirah Mohd Said (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Financial inclusion, which includes the two dimension which is usage and availability of financial services has been thoroughly examined as a possible means of reducing poverty. To illustrate the current status of research in the area of financial inclusion, the previous literature was explored. According to the research that already been conducted, most of it has been done in a particular area, mostly focus on Asian and African countries (developing regions). Very few studies have addressed the Malaysian case. Additionally, as previous research has concentrated on different geographical areas or economic clusters, this study could add to the body of knowledge by presenting a particular case study pertaining to financial inclusion for the purpose of reducing the poverty rate, specifically in Malaysia. So that, this present study utilizes readily accessible secondary data gathered from the World Bank website to acquire information about Malaysia’s financial inclusion achievements. According to the findings from this present study, it is believed that financial inclusion has a potential to reduce poverty rate in Malaysia. Which when there is an increase in offering number of bank branches, ATM machines and access to any financial services it’s able to reduce poverty rate among Malaysian.